Analisis Kemampuan Membaca Pemahaman Evaluatif Siswa Kelas V Sekolah Dasar - Gita Musrial; Chandra Chandra; Inggria Kharisma (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study was conducted because there are still many fifth grade elementary school students who still have difficulty in understanding the contents of the reading, especially when asked to think critically or evaluatively. They have not been able to assess or give opinions about the reading properly. In addition, their reading ability is still low. The purpose of this study was to determine students' ability to understand reading evaluatively. This study used a case study method with a qualitative approach. The researcher involved five fifth grade elementary school students as research subjects. The data for this study were obtained through observation, evaluative reading comprehension ability tests, and documentation. The results of this study indicate that fifth grade students still have low evaluative reading comprehension abilities. Students have not been able to answer questions or complete exercises related to the contents of the reading correctly, have difficulty assessing ideas or ideas conveyed by the author based on their experience and knowledge, cannot state reasons for choosing certain ideas or ideas, and have not been able to compare the main ideas in the text with personal experiences properly. Several factors that cause this low ability are students' difficulty in maintaining concentration while reading, lack of interest and motivation in reading activities, and support provided by the family environment.